2013
DOI: 10.1136/amiajnl-2012-000946
|View full text |Cite
|
Sign up to set email alerts
|

Computerized provider documentation: findings and implications of a multisite study of clinicians and administrators: Table 1

Abstract: ObjectiveClinical documentation is central to the medical record and so to a range of healthcare and business processes. As electronic health record adoption expands, computerized provider documentation (CPD) is increasingly the primary means of capturing clinical documentation. Previous CPD studies have focused on particular stakeholder groups and sites, often limiting their scope and conclusions. To address this, we studied multiple stakeholder groups from multiple sites across the USA.MethodsWe conducted 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…While it has been previously shown that providers believe that there is positive value in using CBD tools for documentation, successful adoption of CBD tools still depends largely on how the tools are implemented [7]. Consistent with findings by Embi et al [10], we found that the note serves as an important form of communication between all stakeholders and there are existing concerns surrounding issues of integrating documentation practices with both provider and administrator workflows. Current development of CBD systems has focused on using structured data entry to facilitate data extraction and communication between multiple parties involved in the care of a patient.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While it has been previously shown that providers believe that there is positive value in using CBD tools for documentation, successful adoption of CBD tools still depends largely on how the tools are implemented [7]. Consistent with findings by Embi et al [10], we found that the note serves as an important form of communication between all stakeholders and there are existing concerns surrounding issues of integrating documentation practices with both provider and administrator workflows. Current development of CBD systems has focused on using structured data entry to facilitate data extraction and communication between multiple parties involved in the care of a patient.…”
Section: Discussionsupporting
confidence: 87%
“…The goal of this study was to expose the knowledge, beliefs and perceptions healthcare providers and administrators have about the value of clinical documentation and the process of documenting. Clinical documentation is a practice that is inextricably shared by both clinical and administrative workflows [10]. To better understand how clinical documentation methods could effectively serve both those who primarily generate notes and those who must review them in today's increasingly multidisciplinary approach to healthcare, we sought perspectives from both healthcare providers and administrators.…”
Section: Introductionmentioning
confidence: 99%
“…For example, medication usage can be identified using electronic orders, pharmacy fulfillment, administration records, or medication reconciliation. EHR data are inherently subject to the institution's workflows and data-generating activities [43][44][45]. For research to be reproducible and for results to be valid, the source and limitations of different types of data within an organization must be clearly defined.…”
Section: Heterogeneity Of Data From Ehrsmentioning
confidence: 99%
“…While the use of EHRs has led to an improvement in quality of healthcare, it has introduced new challenges (Kuhn, Basch et al 2015). One such challenge, ironically, stems from the ease of use of EHRs; the growing use of copy-and-paste, templates, and smart phrases causes clinical notes to bloat in size with poorly organized or erroneous documentation (Embi, Weir et al 2013, Zhang, Pakhomov et al 2014. EHRs are effectively optimized to store massive amounts of information at the cost of adding to the cognitive burden of tracking multiple complex medical problems or maintaining continuity and quality of the clinical decision-making process.…”
Section: Introductionmentioning
confidence: 99%